Reproductive Health and Gynecological Outcomes in Women with Autoimmune and Inflammatory Diseases Receiving DMARD Therapy - Naveed Aslam Lashari, Shandana Altaf, Firdous Ara, Marifat Shah, Munawar Afzal, Sarwat Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Women with autoimmune and inflammatory diseases are at risk for adverse reproductive outcomes due to systemic inflammation and DMARD therapy. Methotrexate has been implicated in gonadotoxicity, yet comprehensive evaluations using modern biomarkers remain limited. Aims and Objectives: This study aimed to determine the prevalence and determinants of gynecological abnormalities and diminished ovarian reserve in women with rheumatic and connective tissue disorders. Specific objectives were to assess menstrual irregularities, sexual dysfunction, and hormonal profiles among patients on various DMARD regimens. Methodology: In a 12‑month prospective observational study at PAF Hospital, Islamabad, n=250 women aged 18–45 years with confirmed diagnoses (rheumatoid arthritis, seronegative RA, psoriatic arthritis, ankylosing spondylitis, systemic lupus erythematosus, Sjögren syndrome, mixed connective tissue disorder, systemic sclerosis) were enrolled. Participants received stable DMARD therapy including traditional agents (methotrexate, leflunomide, sulfasalazine, hydroxychloroquine), biologics, tsDMARDs, JAK inhibitors, and other immunosuppressives. Data were collected via standardized questionnaires, transvaginal ultrasound, and serum measurement of AMH, FSH, estradiol, inhibin B, prolactin, testosterone, and CRP. Statistical analyses were performed using SPSS Model 26 with t-tests, ANOVA, Chi-square tests, and multivariable regression (p < 0.05). Results: Baseline menstrual irregularities were 33%, increasing to 42% at follow‑up. Methotrexate-treated patients had higher irregularity rates (52% vs. 34%; p = 0.01) and significantly lower AMH, higher FSH, reduced estradiol, and decreased inhibin B levels. Conclusion: Systemic inflammation and methotrexate exposure significantly impair reproductive health. Tailored DMARD strategies and integrated reproductive monitoring are essential. Future research should focus on personalized care and fertility outcomes. Keywords: Autoimmune, Inflammatory, DMARDs, Methotrexate, Ovarian Reserve, Menstrual Irregularities, Reproductive Health.